Evaluasi Program Kampung Kb Berbasis Kolaboratif Tata Kelola Pada DP3AKKB Provinsi Banten Studi Kasus di Kota Serang - Diah Karmila; Try Adhi Bangsawan; Dede Qodrat Alwajir (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The Kampung Keluarga Berkualitas (Kampung KB) Program is a strategic government initiative aimed at improving family welfare through integrated and sustainable development. However, its implementation in Serang City continues to encounter challenges related to institutional coordination, stakeholder participation, and resource integration, resulting in suboptimal program outcomes. This study aims to evaluate the implementation of the Kampung KB Program using a collaborative governance perspective at the Regional Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3AKKB) of Banten Province. This research employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and document analysis involving government officials, village governments, family planning counselors, community leaders, and program beneficiaries. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing with triangulation to ensure validity. The findings indicate that collaborative governance has been implemented through cross-sector coordination, stakeholder participation, and community empowerment. Nevertheless, collaboration remains constrained by uneven institutional commitment, limited human resources, insufficient funding, and inconsistent inter-agency communication. The study concludes that strengthening collaborative governance through integrated planning, sustainable stakeholder commitment, and improved coordination mechanisms is essential to enhance the effectiveness and sustainability of the Kampung KB Program in Serang City.